Digital Solutions for Community and Primary Health Workers: Lessons From Implementations in Africa - Owoyemi, Ayomide; Osuchukwu, Joanne I.; Azubuike, Clark; Ikpe, Ronald Kelechi; Nwachukwu, Blessing C.; Akinde, Cassandra B.; Biokoro, Grace W.; Ajose, Abisoye B.; Nwokoma, Ezechukwu Ikenna; Mfon, Nehemiah E.; Benson, Temitope O.; Ehimare, Anthony; et al. (Frontiers in Digital Health, 2022)
The agenda for Universal Health Coverage has driven the exploration of various innovative approaches to expanding health services to the general population. As more African countries have adopted digital health tools as part of the strategic approach to expanding health services, there is a need for defining a standard framework for implementation across board. Therefore, there is a need to review and employ an evidence-based approach to inform managing challenges, adopting best approaches, and implement informed recommendations. We reviewed a variety of digital health tools applied to different health conditions in primary care settings and highlighted the challenges faced, approaches that worked and relevant recommendations. These include limited coverage and network connectivity, lack of technological competence, lack of power supply, limited mobile phone usage and application design challenges. Despite these challenges, this review suggests that mHealth solutions could attain effective usage when healthcare workers receive adequate onsite training, deploying applications designed in an intuitive and easy to understand approach in a manner that fits into the users existing workflows, and involvement of the stakeholders at all levels in the design, planning, and implementation stages of the interventions.